Determining patient prognosis using computed tomography coronary angiography. (September 2011) - Kazmi, Mustapha H; Small, Gary; Sleiman, Lyne; Chow, Benjamin JW
In addition to demonstrating luminal narrowings, cardiac computed tomography angiography (CTA) has the ability to detect nonstenotic plaque, vessel wall calcification and can assess left ventricular function. CTA prognostic studies have considered these components individually and in combination to produce novel risk factor scores to help predict clinical outcomes. In this article, we will consider the utility of CTA to predict clinical risk by considering the evidence for luminal stenosis, plaque scores, plaque descriptors and models combining these elements. We will also discuss some of the emerging applications of CTA that will likely provide future prognostic data in coronary artery disease patients. Although initially described as an anatomical investigation to determine the presence of coronary disease, CTA is being explored as a tool for functional imaging and may soon provide a noninvasive technique of anatomical and functional assessment previously only possible by invasive methods.